PENERAPAN PENYELESAIAN KREDIT MACET MELALUI PROSES PENGALIHAN PIUTANG (CESSIE) DI PT BANK TABUNGAN NEGARA PEKANBARU - Nancy Roseline Manurung; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Cessie is a bad credit settlement process carried out by an old lender where the old lender sells the loan to a new lender. Although cessie is not explicitly mentioned in the Criminal Code but the existence of Article 613 of the Criminal Code makes the cessie process in the world of banking possible, in that case there is a need for a notary deed or deed under the name, but the existence of this act does not create a new lender directly the legal force because the old creditor had to tell the debtor that the debt on his behalf had been transferred to the new lender. This can happen when a debtor performs a transaction, where the debtor does not perform his or her obligation to the lender, and after performing a series of warnings to the debtor and is not advised, the lender can take further action in the form of a debt sale called the term cessie.The research done by the authors is based on the issue of understanding in the implementation of PT. BTN Pekanbaru, and how is the process of performing a loan purchase at PT. BTN. In the process of research the author uses observation and interview methods. The author directly interviews the PT. BTN Pekanbaru. From the findings of the authors' findings it can be concluded that the understanding of the performance of the debt servicing (Cessie) is a consequence of the fact that the debtor's actions are one of the ways that the lender will advertise the cessie, and if any individual or private company buys the cessie then the parties it will be the new lender who will deal further with the lender. Where the debtor is obligated to repay the debt to the new lender. After getting the notification from the old lender in this case is PT. BTN. Where all the rights and position of the old lender will be transferred to the new lender completely. This is a risk to the debtor as a consequence of negligence or failure to comply with its obligations, as cessie is legally bound by Article 613 of the Civil Code. And the way credit lending is resolved against the lender's lending to lenders through several processes is rescheduling, reconditioning, and reorganization which, if not taken by the lender, will be taken by the bank as time goes on. Cessie will be the last choice from the bank to resolve the credit defaulter created by the lender as a form of settlement in the Home Loan Credit agreement previously made by the lender (PT. BTN) and the lenderKeywords: Debt, Agreement, Cessie